Analisis Perbandingan Tiga Metode Evaluasi Usability Dalam Mencari Permasalahan Usability (Studi Kasus: Aplikasi Situbondo Tera') - Farid Khatibul Umam; Fatwa Ramdani; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Situbondo Tera' is a portal application of the Situbondo Regency Government that can be accessed by the public. Based on the researcher's experiment and interviews with the developer the application is still not running optimally and has never been evaluated. This study uses 3 methods, those are Usability Testing, Cognitive Walkthrough, and Heuristic Evaluation to find usability problems and see the comparison of the problems obtained from each method. The study used 10 respondents on Usability Testing, 10 respondents on Cognitive Walkthrough, and 3 experts on the Heuristic Evaluation method. From the analysis it is known that total of 41 problems were found. The Usability Testing method found 27% of the total problems with an average of 2.4 problems per respondent. The Cognitive Walkthrough method found 29% of the total problems with an average finding of 3.7 problems per respondent. Meanwhile, the Heuristic Evaluation method found 44% of the total problems with an average finding of 8 problems per evaluator. There were 8 similar problems found and almost all of them appeared in 3 methods at once so that it needed special attention. The results of the Usability Testing method got an average value of 95% effectiveness, 88.32% efficiency, and the satisfaction gets 5.76 from scale 1 to 7. In the Cognitive Walkthrough method, it was known that the problems that often arise were minor and most types of the problems come from Text and Icon (T) and User (U). The Heuristic Evaluation method found problems that were spread across all 9 heuristic principles.